Vaksin Covid-19 Pada Ibu Hamil - Siti Nurkomala Sari; Nurul Islamy (CV. Jasa Sukses Abadi, 2021)
Coronavirus disease 2019 is an acute respiratory syndrome that causes severe, moderate or mild symptoms. This infection is susceptible in pregnant women and it is associated with the risk of morbidity and mortality both in mother and baby such as intensive care unit, preeclampsia, infection and premature birth and low birth weight. This condition can be prevented by administering the covid-19 vaccine to pregnant women. The covid-19 vaccine is divided into three types based on the mechanism of action, which are mRNA, viral vector and recombinant protein antigen. Four covid-19 vaccines are approvedfor use in the UK; the Pfizer-BioNTech vaccine, the Oxford-AstraZeneca vaccine, the Moderna vaccine and the Janssen vaccine. The vaccine recommended for pregnant women in Indonesia is the Sinovac vaccine which uses the inactivated COVID-19 virus to trigger an immunological response in host cells.